Genetic Investigations in Turkish Idiopathic Pancreatitis Patients Show Unique Characteristics - Hasan Baş,; Hasan Baş,; Selçuk Dişibeyaz,; Erkin Öztaş,; Yusuf Aydemir,; Tuncer Temel,; Oğuz Çilingir,; Beyhan Durak Aras,; Sevilhan Artan, (Turkish Journal of Gastroenterology, 2023)
Background/Aims: Pancreatitis is one of the leading causes of digestive system-related hospital admissions, and it has a genetic background in a considerable portion of the patients. In this study, we aimed to investigate the genetic risk factors of idiopathic pancreatitis in Turkish patients and the contribution of copy number variations to the pathogenesis. Materials and Methods: Idiopathic pancreatitis is defined as failure to detect risk factors despite comprehensive clinical assessments. Next-generation sequencing and multiple ligand-dependent probe amplification of PRSS1, SPINK1, CTRC, and CFTR were performed. For further genotype–phenotype correlations, patients were also questioned for the age of onset, family history, and pancreatic divisum. Results: A total of 68 idiopathic pancreatitis cases were enrolled. Variants with potential clinical significance of PRSS1 were identified in 13.4%, SPINK1 in 6.3%, CTRC in 4.7%, and CFTR in 26.5% of the patients. No copy number variants were seen in any of these genes. At least 7.4% of the participants had complex genetic etiology involving 2 genes. Conclusions: At least 42.6% of the participants had a potential genetic risk factor. Five novel genetic variants were identified, and distinctive genetic risk factors of Turkish population were shown. The results showed that genetic etiology was frequent in pancreatitis and it was even more prominent in patients with early-onset disease. Considering that genetic risk factors may be informative for decisionmaking in the treatment options in addition to providing extensive prognostic value and familial genetic consultation; clinicians need to be more eager to offer genetic tests to pancreatitis patients. Cite this article as: Baş H, Dişibeyaz S, Öztaş E, et al. Genetic investigations in Turkish idiopathic pancreatitis patients show unique characteristics. Turk J Gastroenterol. 2023;34(12):1240-1248.